Faktor – Faktor Yang Mempengaruhi Kejadian PEB Pada Pasien Rawat Inap Diruang ICU - Yuyun Setyorini; Martono Martono; Imelda Wijayanti ((JKG) Jurnal Keperawatan Global, 2016)
Abstrack: Factor - The Influence Of Factors, Incidence Of PEB. ICU is and intensive room used to take care patients that need nursing and special treatment, on the critical condition and having a chance to be saved. The writer got the data from ICU RSUD Dr. Moewardi Hospital of Surakarta that there is an increastment of PEB victims from year 2010 to 2011 where the number of PEB victims on 2010 were 9 patients and on 2011 were were 79 patients. This study aims to clarify between the two dependent variables and independent through hypothesis testing at the time was past, so this type of research is to design Eksplantory Reserver retrospectively. The research was conducted by Chi Square test. There are not relation between factors that influence incident of PEB to patient in treatment in ICU room of RSUD Dr. Moewardi Surakarta. There was no effect of the relationship between the incidence of PEB by a factor of gravida, distension of the uterus, a history of comorbid disease, maternal age and parity in patients hospitalized in the ICU Hospital Dr. Moewardi Surakarta.